Effects of Training and Supervision on Work Performance among Health Workers in Hospital: Meta-Analysis - Luturmas, Antina; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Performance in an organization is carried out by all existing human resources, both leaders and workers. There are several factors that can affect human resources in carrying out their performance, both factors that come from within human resources and those that come from outside themselves. The purpose of this study was to analyze the effect of training and supervision on the performance of health workers in hospitals, using a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This article was prepared using a systematic review and meta-analytic study. This research was conducted using the PICO model. The meta-analytic study was carried out by searching for articles from databases in electronic form using Google scholar, PubMed, Science direct, and Springerlink. An article search was conducted from 1 to 18 February 2023. The keywords used were “Performance” AND “Training” AND “supervision” AND “health workers” AND “Multivariate” AND “Cross-Sectional”. The inclusion criteria for this study were complete articles using cross-sectional research, published years from 2013-2023. Analysis of the articles in this study used RevMan 5.3 software. Results: A total of 10 cross-sectional studies from Africa and Asia were selected for systematic review and meta-analysis. The results of the meta-analysis show that training can improve performance and supervision can improve performance. Health workers who received training had a large influence on improving performance by 1.68 compared to those who did not receive training (aOR= 1.68; 95% CI= 1.37 to 2.05; p= 0.001). Supervised health workers had an influence on improving performance 2.38 times compared to unsupervised health workers (aOR= 2.38; 95% CI= 1.57 to 3.61; p= 0.009). Conclusion: Training can improve performance and supervision can improve health worker performance. Keywords: Performance, training, supervision, health workers Correspondence: Antina Luturmas, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: antinaluturmas@gmail.com. Mobile: +6282387204089